Fabrication of functional nanosized patterns with UV-curable polysilsesquioxane on photovoltaic protective glass substrates using hybrid nano-imprint lithography - Shin, Ju-Hyeon; Go, Bit-Na; Choi, Hak-Jong; Cho, Joong-Yeon; Lee, Albert Sung Soo; Hwang, Seung Sang; Cha, Hyuk Jin; Lee, Heon (ROYAL SOC CHEMISTRY, 2014)
UV-curable polysilsesquioxane materials were used to incorporate moth-eye structures on photovoltaic (PV) protective glass. These patterns were formed using a hybrid nanoimprint lithography technique and annealed at 100 degrees C to evaporate the solvent (xylene). Compared to the bare, un-patterned PV protective glass, the PV protective glass patterned on both sides had superior optical properties. Transmittance of the PV protective glass patterned on both sides increased by up to 3.13% and reflectance decreased by up to 3.42%, and the transmittance was increased for all angles of incidence. Furthermore, the JSC of devices with the PV protective glass patterned on both sides increased by up to 3.15%. Finally, a monitoring system was set up to measure electricity generated by PV modules. The efficiency of the PV module with PV protective glass patterned on both sides was enhanced by up to 12.16% compared with that of the PV module with un-patterned PV protective glass.
Keywords: SILICON SOLAR-CELLS; INTERFERENCE LITHOGRAPHY; EFFICIENCY; OPTIMIZATION; LIGHT